A Facile and Convenient Synthesis of (±)-Biotin via MgCl2/Et3N-Mediated C–C Coupling and Mitsunobu Reaction - Chavan, Subhash P.; Chavan, Prakash N.; Lasonkar, Pradeep B.; Khairnar, Lalit B.; Kadam, Appasaheb L. (Synlett, 2014)
A synthesis of (±)-biotin is described starting from simple starting materials viz. cyclohexanone and amino malonic acid ester. The key steps involved are MgCl2/Et3N coupling of amino malonic acid ester derivative and acid chloride, Mitsunobu reaction, ozonolysis, Staudinger reduction, novel urea formation, and subsequent dibenzylation. This approach is economical and involves high-yielding steps and simple reaction conditions.
Keywords: biotin; ozonolysis; Appel reaction; Mitsunobu reaction; Staudinger reduction